Africa : an encyclopedia of culture and society - Falola, Toyin; Jean-Jacques, Daniel (Santa Barbara, California : ABC-CLIO, an imprint of ABC-CLIO, LLC, 2016)
"These volumes offer a one-stop resource for researching the lives, customs, and cultures of Africa's nations and peoples. Unparalleled in its coverage of contemporary customs in all of Africa, this multivolume set is perfect for both high school and public library shelves. The three-volume encyclopedia will provide readers with an overview of contemporary customs and life in North Africa and sub-Saharan Africa through discussions of key concepts and topics that touch everyday life among the nations' peoples. While this encyclopedia places emphasis on the customs and cultural practices of each state, history, politics, and economics are also addressed. Because entries average 14,000 to 15,000 words each, contributors are able to expound more extensively on each country than in similar encyclopedic works with shorter entries. As a result, readers will gain a more complete understanding of what life is like in Africa's 54 nations and territories, and will be better able to draw cross-cultural comparisons based on their reading."--Publisher's description.
V. 1. Algeria-Djibouti -- v. 2. Egypt-Mozambique -- v. 3. Namibia-Zimbabwe.
Includes bibliographical references and index.
Keywords: Africa -- Civilization -- Encyclopedias; Africa -- Encyclopedias